Educação inovadora: uma possibilidade na EPT - Serrão, Yoli Glenda da Silva (2019)
Professional and Technological Education has historically been associated with compensatory education for the working class; however, many educators have tried to build teaching based on a methodology that allows the construction of a less unequal and more participative society. This bibliographic, documentary and descriptive research aims to analyze the contributions of participatory planning to the implementation of the Escola da Ponte Methodology in EPTNM Courses at IFAM, as well as the importance of re-signifying teachers for this break of paradigms based so strongly on professional education. The theoretical contribution was based on the ideas and perceptions of authors such as Paulo Freire, Saviani, Ciavatta, José Pacheco, among others. The methodology used in this research with regard to the approach is qualitative; as for nature it is Basic; in relation to the objectives, it is of the Descriptive type, with bibliographic and documentary research procedures, with direct observation to two of the schools described in the present work. To analyze the data collected in publications and audiovisuals, Content Analysis and some theoretical assumptions of Textual Discourse Analysis are used, with a predominance of thematic content analysis. Being a research of phenomenological methodology, since it uses the experiences of students and educators published in books and other audiovisual documents. As an educational product, the preparation of an orientation booklet regarding Participatory Planning in the Escola da Ponte Methodology and its implications for Professional and Technological Education (EPT) was considered.